Estudio sobre la patogenicidad de Fusarium oxysporum f. phaseoli en el frijol. I. Patogénesis e histología sintomatológica - López Duque, S.; Muller, L.E. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
The penetration development of the infection in the pathological anatomy of the so-called “fusariosis” disease of the common bean was to studied in several susceptible and tolerant varieties. The tests of penetration were performed both in vitro and in plants grown in sterilized soil, utilizing nine different methods of inoculation. Penetration can occur through the root of the hypocotyl but the presence of wounds is necessary in order to permit penetration into exposed xyleme vessels. Microscopic observation of cut and mounted sections revealed that the fungus grows principally inside the vascular elements, causing discoloration and browning of the affected areas. Subsequent deposits of gum-like materials and cause plugging of the vascular system. No anatomical differences could be observed between tolerant and susceptible varieties. There were, however, apparent differences with respect to both external and internal symptoms. In varieties that show dwarfing and stunting little Browning Accord and symptoms that show dwarfing or stunting, little browning occurred and about 43 per cent of the vascular vessels were obstructed, whereas in plants with yellowing 67 per cent were obstructed together with browning symptoms of moderate intensity, and in those with severe wilting almost 80 per cent of the vessels were obstructed. It was concluded that tolerance is due to physiological mechanisms rather than to the formation of physical barriers which could impede growth of the fungus within the host